Peningkatan Pengetahuan Perilaku Hidup Bersih dan Sehat Rumah Tangga - Wulan Angraini; Henni Febriawati; Muhammad Amin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the increase in knowledge of household clean and healthy behavior in an effort to create a healthy family at the UPTD Puskesmas Kuala Lemruban, Bengkulu City. This research method is a descriptive study with a cross sectional design. The results of the research on health education at the pre-test were 57.69 and the mean post-test was 74.62 with a p-value of 0.000. In conclusion, there is a significant effect of health education on Clean and Healthy Life Behavior in UPTD Puskesmas Kuala Lemruban, Bengkulu City. Keywords: Improvement, Counseling, Clean and Healthy Life Behavior